Method for simulating MAX phase directional arrangement in Ag / MAX electric contact material plastic deformation process

Gleeble thermal simulation technology simulates the plastic deformation process of Ag/MAX electrical contact materials, realizes the orientation arrangement of MAX phases, solves the problem of poor performance of existing materials in high temperature and high humidity environments, and significantly improves the conductivity and resistance of the materials Arc erosion.

CN119492732APending Publication Date: 2025-02-21CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566084.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing Ag-based electrical contact materials have poor performance in high temperature and high humidity environments, and the materials enhanced phase distribution prepared by powder metallurgy method is random, making it difficult to achieve directional arrangement, resulting in insufficient performance.

Method used

Gleeble thermal simulation technology is used to simulate the plastic deformation process of Ag/MAX electrical contact materials, and the MAX phase is realized by setting different deformation temperatures and strain rates.

Benefits of technology

By orientingly aligning the MAX phases, the conductivity, arc corrosion resistance and overall performance of the Ag/MAX electrical contact materials are significantly improved, shortening the development cycle and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for simulating MAX phase directional arrangement in a plastic deformation process of an Ag / MAX electric contact material. The plastic deformation process of the Ag / MAX composite material is simulated through a Gleeble thermal simulation test, and the evolution of the microscopic structure of the material at different deformation temperatures and deformation rates, including the directional arrangement degree of the MAX phase, is analyzed. When the method is used for simulating and predicting the MAX phase directional arrangement in the Ag / MAX composite material plastic deformation process, theoretical guidance can be provided for the Ag / MAX composite material deformation process. Directional arrangement of a reinforced phase MAX is realized through a plastic deformation process, so that the conductivity, arc erosion resistance and other properties of the Ag / MAX electric contact material are improved. The method is suitable for a small-size sample, the material consumption of the Ag / MAX composite material can be reduced, the precious metal Ag resource is saved, and the research and development period of the Ag / MAX electric contact material with the MAX phase in highly directional arrangement prepared through plastic deformation is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic deformation preparation of electric contact materials, and in particular relates to a method for simulating the directional arrangement of a reinforcement phase (MAX phase) in a plastic deformation process of an Ag / MAX composite material. Background Art

[0002] Ag-based electrical contact materials are widely used in low-voltage circuits, but their application is greatly limited due to the low hardness and low wear resistance of silver itself, as well as the fact that silver sulfide is easily generated under high temperature and high humidity conditions. At present, adding other elements or reinforcing phases is a common method to improve the hardness, resistance to welding, and resistance to arc erosion of silver-based electrical contact materials. The MAX phase has the excellent properties of both metals and ceramics, with good electrical and thermal conductivity, moderate hardness, and non-toxicity. It can be used as an excellent reinforcing phase for Ag-based composite materials. A large number of studies have shown that Ag / MAX electrical contact materials have demonstrated their excellent electrical conductivity and resistance to arc erosion.

[0003] For most electrical contact materials prepared by powder metallurgy, the distribution and arrangement direction of the reinforcement phase in the matrix are random, and defects such as pores and impurities are inevitable. Therefore, subsequent plastic deformation is the key to adjusting the distribution and orientation of the reinforcement phase, eliminating material microscopic defects, and improving performance. In addition to in-depth research on the interface reaction and arc erosion mechanism of Ag / MAX, optimizing and regulating the organization and properties of Ag / MAX electrical contact materials is also one of the important ways to develop Ag / MAX electrical contact materials. Compared with ordinary powder metallurgy methods, sintering extrusion can make the prepared Ag / C and other materials have better performance. This is because the arrangement direction of the reinforcement phase has a significant effect on the arc erosion resistance of the material. Yu et al. (Yu et al., Journal of Alloys and Compounds, 2018, 732: 894-901) used hot extrusion technology to make Ti2AlC particles form a directional arrangement in the matrix. Based on the anisotropy of the MAX phase, Ag / MAX composite materials with a high degree of oriented MAX phase have better performance in specific directions (Wang et al., Journal of Alloys and Compounds. 2019, 784:431-438.). The preparation of Ag / MAX materials by large plastic deformation method to achieve oriented arrangement of MAX phase helps to provide performance optimization strategies for Ag / MAX materials. However, in the traditional production process, it is difficult to accurately control the deformation rate, deformation temperature, deformation amount, etc. for obtaining oriented organization, which usually requires multiple tests, resulting in a long development cycle and high cost.

[0004] Gleeble thermal simulation provides analytical data that not only reveals the microscopic mechanism but also guides the actual process for physical metallurgical research and scientific research and development of metal materials by simulating the deformation behavior of small metal samples under different heating and stress conditions. By setting different strain rates and temperatures, the plastic deformation process of the material under these parameters can be simulated. Summary of the invention

[0005] Based on the problems pointed out in the background technology, the purpose of the present invention is to provide a method for simulating the oriented arrangement of MAX phase during plastic deformation of Ag / MAX electrical contact materials. By performing Gleeble simulation on Ag / MAX composite materials and combining microstructure analysis after simulated deformation, guidance can be provided for the plastic deformation process of preparing Ag / MAX electrical contact materials with oriented arrangement of MAX phase, thereby greatly shortening the development cycle of new materials and new processes and reducing development costs.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows: A method for simulating the oriented arrangement of MAX phases during the plastic deformation process of Ag / MAX electrical contact materials comprises the following steps: Step S1: weighing Ag powder and MAX phase powder according to a certain ratio, mixing the powders by ball milling, and then fully mixing the powders to obtain mixed powder; Step S2: placing the mixed powder into a mold, and obtaining the Ag / MAX material by rapid hot pressing and sintering under an inert atmosphere or vacuum protection; Step S3: Processing the Ag / MAX material obtained by sintering into a Gleeble compression test sample; Step S4: welding a thermocouple to the surface of the material to observe the temperature change of the material in real time; Step S5: adding lubricant to the contact parts between the two ends of the Gleeble compression specimen and the fixture; fixing the Gleeble compression specimen on the fixture of the Gleeble thermal simulation test machine; Step S6: setting the required test parameters in the Gleeble thermal simulation test machine, performing a compression test, and then rapidly cooling the sample; Step S7: cutting, grinding, and polishing the Gleeble compression specimen, observing its microstructure, and obtaining the evolution of the specimen microstructure under different experimental parameters.

[0007] As one of the preferred solutions of the above technical solution, in step S1, the MAX phase accounts for 5-50wt.% of the total weight of the mixed powder.

[0008] As one of the preferred solutions of the above technical solution, in step S1, the ball milling method is a wet milling method or a dry milling method, and the ball milling time is 0.5-24 h.

[0009] As one of the preferred solutions of the above technical solution, in step S2, the temperature of the rapid hot pressing sintering is 500-900°C, the sintering pressure is 10-50 MPa, and the holding time is 5-60 min.

[0010] As one of the preferred solutions of the above technical solution, in step S3, the Gleeble compression test sample can be a cylindrical sample or a rectangular parallelepiped sample, and the size of the sample is preferably 1.5 to 2 times the diameter. The surface of the Gleeble compression test sample needs to be polished with 2000# or above sandpaper.

[0011] As one of the preferred schemes of the above technical scheme, in step S4, the thermocouple installation method is selected according to the electrical conductivity of the material. The material with a sample conductivity ≥1 MS / m can effectively conduct heat, making the measurement of the thermocouple more accurate, and the thermocouple can be directly welded to the center of the central axis of the sample; if the material with a sample conductivity <1 MS / m, a hole is drilled in the center of the central axis of the sample to install the thermocouple.

[0012] Preferably, the diameter of the thermocouple should be ≤ 0.5 mm to avoid thermal influence and mechanical disturbance on the sample.

[0013] Preferably, the thermocouple is a K-type thermocouple.

[0014] As one of the preferred solutions of the above technical solution, in step S5, the lubricant is not limited to lubricants such as graphite or mica, which can reduce the friction on the end surface of the sample and the bulging in the middle, thereby ensuring the accuracy of compression physical simulation.

[0015] As one of the preferred solutions of the above technical solution, in step S6, the thermal simulation compression test is: heating the thermal compression sample to the deformation temperature at a heating rate of 5-30 ℃ / s, keeping the temperature for 5-30 min, and then performing the thermal compression test at the strain rate, and water cooling. The engineering strain is ≤60% to prevent the thermocouple from falling off; As one of the preferred solutions of the above technical solution, in step S6, the deformation temperature is 200-900°C, the strain rate is 10 -3 s -1 -30 s -1 .

[0016] The present invention also provides the application of the method for simulating the oriented arrangement of MAX phase in the plastic deformation process of Ag / MAX electrical contact material in guiding the plastic deformation process of preparing Ag / MAX electrical contact material with oriented arrangement of MAX phase.

[0017] Beneficial Effects

[0018] (1) Ag / MAX electrical contact materials can achieve oriented arrangement of MAX phases during plastic deformation, which helps to improve the electrical conductivity and arc erosion resistance of the material and significantly improve its electrical contact performance. Based on Gleeble thermal simulation technology, the present invention can effectively predict the oriented arrangement of MAX phases in Ag / MAX composite materials at different deformation temperatures and deformation rates. By analyzing the evolution of the material microstructure, this method provides theoretical guidance for optimizing the deformation process of Ag / MAX composite materials, thereby achieving more precise process control and performance optimization.

[0019] (2) This method is suitable for simulation prediction of small-volume samples, which can effectively reduce the actual materials used for Ag / MAX composite materials and save precious metal silver resources. This not only reduces R&D costs, but also improves resource utilization. Compared with traditional experimental methods, it is more efficient and can quickly evaluate the microstructural changes and performance improvements of materials under different process parameters, shortening the R&D cycle.

[0020] (3) The present invention applies thermal simulation technology to Ag / MAX composite materials. By controlling the plastic deformation process parameters, the arrangement of the reinforcement phase can be adjusted. This directional arrangement can improve the mechanical properties and electrical conductivity of the material, further improving the overall performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The deformation temperature is 600 °C and the strain rate is 0.001 s -1 Microstructure diagram of .

[0022] Figure 2 The deformation temperature is 600 °C and the strain rate is 1 s -1 Microstructure diagram of .

[0023] Figure 3 The deformation temperature is 400 °C and the strain rate is 0.001 s -1 Microstructure diagram of .

[0024] Figure 4 The deformation temperature is 400 °C and the strain rate is 1 s -1 Microstructure diagram of . DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below. The following description is only for understanding the technical solution of the present invention and is not intended to limit the scope of the present invention. The protection scope of the present invention shall be subject to the claims.

[0026] The present invention provides a method for simulating the oriented arrangement of MAX phase during plastic deformation of Ag / MAX electrical contact material, which is applied to the compression test of Ag / Ti3AlC2 and reasonably improved according to the temperature and strain rate set in the Gleeble compression test and the corresponding microstructure. Taking Ag-10 wt.%Ti3AlC2 electrical contact material as an example. Specifically, the method includes the following steps: (1) Ag powder and Ti3AlC2 phase powder were weighed in a mass ratio of 9:1 and mixed by wet ball milling for 30 min. Then, the powders were sintered at 800 °C for 20 min under an inert atmosphere or vacuum protection and a pressure of 20 MPa.

[0027] (2) Processing and preparation of Gleeble compression specimens: The sintered Ag / Ti3AlC2 wire was cut into Φ8 mm × h 12 mm cylindrical specimens. The upper and lower surfaces of the specimens were polished with 2000# sandpaper. The height direction of the cylinder was the sintering direction of the sample. (3) Considering the influence of friction during the compression process, a graphite lubricant is applied to the end surface of the Gleeble thermal simulation compression specimen for lubrication; the Gleeble compression specimen is fixed on the fixture of the Gleeble thermal simulation test machine; (4) Experimental parameters were set on a Gleeble 3500 thermal simulation test machine: the temperature was raised to the preset temperature at a rate of 20 °C / s and kept at that temperature for 10 min, and then the strain rate was set at 0.001-1 s -1 Compression tests were carried out with an engineering strain of 50%, and finally water-cooled to room temperature to retain the microstructure at high temperature.

[0028] (5) Cut the compressed sample along the direction perpendicular to the compression and observe the microstructure of the sample. Example 1

[0029] A method for simulating the oriented arrangement of MAX phases during plastic deformation of Ag / MAX electrical contact materials is applied to a compression test of Ag / Ti3AlC2. The embodiment specifically includes the following steps: (1) Ag powder and Ti3AlC2 phase powder were weighed in a mass ratio of 9:1 and mixed by wet ball milling for 30 min. Then, the powders were sintered at 800 °C for 20 min under an inert atmosphere or vacuum protection and a pressure of 20 MPa.

[0030] (2) Gleeble compression test samples of Ag / Ti3AlC2 were processed and prepared, and the upper and lower surfaces of the samples were polished with 2000# sandpaper; the Gleeble hot compression in this embodiment is a unidirectional compression experiment, and the Gleeble hot compression test sample prepared is a cylindrical sample with a size of Φ8 mm×12 mm, and the sampling direction is the sintering direction of the sample; (3) Considering the influence of friction during the compression process, a graphite lubricant is applied to the end surface of the Gleeble thermal simulation compression specimen for lubrication; the Gleeble compression specimen is fixed on the fixture of the Gleeble thermal simulation test machine; (4) Experimental parameters were set on a Gleeble 3500 thermal simulation test machine: the temperature was raised to 600°C at a rate of 20°C / s and kept at that temperature for 10 min, and then the temperature was increased at a strain rate of 0.001 s -1 Compression tests were carried out with an engineering strain of 50%, and finally water-cooled to room temperature to retain the microstructure at high temperature.

[0031] (5) The compressed sample was cut along the direction perpendicular to the compression direction and the microstructure of the sample was observed. Under the set experimental parameters, the Ti3AlC2 in Ag / Ti3AlC2 was arranged in a disordered manner, the aspect ratio of the particles was mainly concentrated in the range of 1.2-2.7, and the particle size was 11.2±7.3 μm. Example 2

[0032] This embodiment specifically includes the following steps: (1) Ag powder and Ti3AlC2 phase powder were weighed in a mass ratio of 9:1, and the mixed powders were mixed by wet ball milling for 30 min. Then, the mixed powders were sintered at 800 °C for 20 min under an inert atmosphere or vacuum protection and a pressure of 20 MPa.

[0033] (2) Gleeble compression test samples of Ag / Ti3AlC2 were processed and prepared, and the upper and lower surfaces of the samples were polished with 2000# sandpaper; the Gleeble hot compression in this embodiment is a unidirectional compression experiment, and the Gleeble hot compression test sample prepared is a cylindrical sample with a size of Φ8 mm×12 mm, and the sampling direction is the sintering direction of the sample; (3) Considering the influence of friction during the compression process, a graphite lubricant is applied to the end surface of the Gleeble thermal simulation compression specimen for lubrication; the Gleeble compression specimen is fixed on the fixture of the Gleeble thermal simulation test machine; (4) The experimental temperature was set to 600 °C in the Gleeble 3500 thermal simulation test machine. Before the start of thermal compression, the temperature was raised to the preset temperature at a rate of 20 °C / s and kept at this temperature for 10 min. The strain rate was 1 s -1 , the engineering strain is 50%, and finally water-cooled to room temperature to retain the microstructure at high temperature.

[0034] (5) The compressed sample was cut along the direction perpendicular to the compression direction, and the microstructure of the Ag / Ti3AlC2 electrical contact material under the set experimental parameters could be observed. Under the set experimental parameters, the degree of directional arrangement of Ti3AlC2 in Ag / Ti3AlC2 was low, the aspect ratio of the particles was mainly concentrated in 1.3-1.9, and the particle size was 12.5±7.7 μm. Example 3

[0035] This embodiment specifically includes the following steps: (1) Ag powder and Ti3AlC2 phase powder were weighed in a mass ratio of 9:1, and the mixed powders were mixed by wet ball milling for 30 min. Then, the mixed powders were sintered at 800 °C for 20 min under an inert atmosphere or vacuum protection and a pressure of 20 MPa.

[0036] (2) Gleeble compression test samples of Ag / Ti3AlC2 were processed and prepared, and the upper and lower surfaces of the samples were polished with 2000# sandpaper; the Gleeble hot compression in this embodiment is a unidirectional compression experiment, and the Gleeble hot compression test sample prepared is a cylindrical sample with a size of Φ8 mm×12 mm, and the sampling direction is the sintering direction of the sample; (3) Considering the influence of friction during the compression process, a graphite lubricant is applied to the end surface of the Gleeble thermal simulation compression specimen for lubrication; the Gleeble compression specimen is fixed on the fixture of the Gleeble thermal simulation test machine; (4) The experimental temperature was set to 400 °C in the Gleeble 3500 thermal simulation test machine. Before the start of thermal compression, the temperature was raised to the preset temperature at a rate of 20 °C / s and kept at this temperature for 10 min. The strain rate was 0.001 s -1 , the engineering strain is 50%, and finally water-cooled to room temperature to retain the microstructure at high temperature.

[0037] (5) The compressed sample was cut along the direction perpendicular to the compression, and the microstructure of the Ag / Ti3AlC2 electrical contact material under the set experimental parameters could be observed. Under the set experimental parameters, the Ti3AlC2 arrangement degree in Ag / Ti3AlC2 was low, the aspect ratio of the particles was mainly concentrated in the range of 1.5-2.7, and the particle size was 13.3±8.7 μm. Example 4

[0038] This embodiment specifically includes the following steps: (1) Ag powder and Ti3AlC2 phase powder were weighed in a mass ratio of 9:1, and the mixed powders were mixed by wet ball milling for 30 min. Then, the mixed powders were sintered at 800 °C for 20 min under an inert atmosphere or vacuum protection and a pressure of 20 MPa.

[0039] (2) Gleeble compression test samples of Ag / Ti3AlC2 were processed and prepared, and the upper and lower surfaces of the samples were polished with 2000# sandpaper; the Gleeble hot compression in this embodiment is a unidirectional compression experiment, and the Gleeble hot compression test sample prepared is a cylindrical sample with a size of Φ8 mm×12 mm, and the sampling direction is the sintering direction of the sample; (3) Considering the influence of friction during the compression process, a graphite lubricant is applied to the end surface of the Gleeble thermal simulation compression specimen for lubrication; the Gleeble compression specimen is fixed on the fixture of the Gleeble thermal simulation test machine; (4) The experimental temperature was set to 400 °C in the Gleeble 3500 thermal simulation test machine. Before the start of thermal compression, the temperature was raised to the preset temperature at a rate of 20 °C / s and kept at that temperature for 10 min. The strain rate was 1 s -1 , the engineering strain is 50%, and finally water-cooled to room temperature to retain the microstructure at high temperature.

[0040] (5) The compressed sample was cut along the direction perpendicular to the compression, and the microstructure of the Ag / Ti3AlC2 electrical contact material under the set experimental parameters could be observed. Under the set experimental parameters, the Ti3AlC2 in Ag / Ti3AlC2 had a high degree of directional arrangement, the aspect ratio of the particles was mainly concentrated in the range of 1.3-3, and the particle size was 13.1±8.5 μm.

[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for simulating the oriented arrangement of MAX phase during plastic deformation of Ag / MAX electrical contact material, characterized in that: The following steps are involved: Step S1: weighing Ag powder and MAX phase powder according to a certain ratio, and mixing them evenly by ball milling to obtain mixed powder; Step S2: placing the mixed powder into a mold, and obtaining the Ag / MAX material by rapid hot pressing and sintering under an inert atmosphere or vacuum protection; Step S3: Processing the Ag / MAX material obtained by sintering into a Gleeble compression test sample; Step S4: installing a thermocouple on the surface of the Gleeble compression specimen; Step S5: Fixing the Gleeble compression specimen on the fixture of the Gleeble thermal simulation test machine; Step S6: setting the required test parameters in the Gleeble thermal simulation test machine, performing a compression test, and then rapidly cooling the sample; Step S7: cutting, grinding, and polishing the Gleeble compression specimen, observing its microstructure, and obtaining the evolution of the specimen microstructure under different experimental parameters.

2. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: In step S1, the MAX phase accounts for 5-50 wt.% of the weight of the mixed powder; the ball milling method is wet milling or dry milling, and the ball milling time is 0.5-24 h.

3. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: In step S2, the temperature of the rapid hot pressing sintering is 500-900°C, the sintering pressure is 10-50 MPa, and the holding time is 5-60 min.

4. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: In step S3, the Gleeble compression specimen is processed and prepared into a cylindrical specimen or a rectangular specimen; the aspect ratio of the Gleeble compression specimen is 1.5-2.

5. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: In step S4, the installation method of the thermocouple is selected according to the conductivity of the material: for materials with a sample conductivity of ≥1 MS / m, the thermocouple is directly welded to the center of the central axis of the sample; for materials with a sample conductivity of <1 MS / m, a hole is drilled in the center of the central axis of the sample to install the thermocouple.

6. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1 or 5, characterized in that: The diameter of the thermocouple is ≤ 0.5 mm.

7. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: The step S5 also includes adding lubricant to the contact parts between the two ends of the Gleeble compression specimen and the fixture.

8. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: The test parameters in step S6 are as follows: the temperature of the thermal simulation test is 200-900 °C, the heating rate is 5-30 °C / min, the holding time is 5-30 min; the strain rate is 10 -3 -30 s -1 , engineering strain ≤60%.

9. The method for simulating MAX phase orientation during plastic deformation of Ag / MAX electrical contact material according to claim 1, characterized in that: The method is suitable for simulation prediction of small volume samples.

10. Use of the method for simulating oriented arrangement of MAX phase during plastic deformation of Ag / MAX electrical contact material according to any one of claims 1 to 9 in guiding the preparation of Ag / MAX electrical contact material with oriented arrangement of MAX phase.